Association of obstructive sleep apnea with microvascular endothelial dysfunction and subclinical coronary artery disease in a community-based population. (August 2018) - Shpilsky, Daniel; Erqou, Sebhat; Patel, Sanjay R; Kip, Kevin E; Ajala, Oluremi; Aiyer, Aryan; Strollo, Patrick J; Reis, Steven E; Olafiranye, Oladipupo
Studies have reported an association between obstructive sleep apnea (OSA) and cardiovascular disease (CVD) morbidity and mortality. Proposed mechanisms include endothelial dysfunction and atherosclerosis. We aimed to investigate the associations of OSA with endothelial dysfunction and subclinical atherosclerotic coronary artery disease (CAD), and assess the impact of race on these associations. We used data from the Heart Strategies Concentrating on Risk Evaluation (Heart SCORE) study, a community-based prospective cohort with approximately equal representation of black and white participants. OSA severity was measured in 765 individuals using the apnea-hypopnea index (AHI). Endothelial dysfunction was measured using the Endo-PAT device, expressed as Framingham reactive hyperemia index (F_RHI). Coronary artery calcium (CAC), a marker of subclinical CAD, was quantified by electron beam computed tomography. There were 498 (65%) female participants, 282 (37%) black individuals, and 204 (26%) participants with moderate/severe OSA (AHI ≥15). In univariate models, moderate/severe OSA was associated with lower F_RHI and higher CAC, as well as several traditional CVD risk factors including older age, male sex, hypertension, diabetes, higher body mass index, and lower high-density lipoprotein cholesterol levels. In a multivariable model, individuals with moderate/severe OSA had 10% lower F_RHI and 35% higher CAC, which did not reach statistical significance ( p =0.08 for both comparisons). There was no significant interaction of race on the association of OSA with F_RHI or CAC ( p -value >0.1 for all comparisons). In a community-based cohort comprised of black and white participants, moderate/severe OSA was modestly associated with endothelial dysfunction and subclinical atherosclerotic CAD. These associations did not vary by race.